Hubungan Durasi Penyakit dan Kadar Gula Darah Dengan Keluhan Subyektif Pada Penderita Diabetes Mellitus Tipe II di Puskesmas Putri Ayu Kota Jambi - Hasnita Hasnita; Rasyidah A Z; Ani Astuti (STIKes Karsa Husada Garut, 2020)
Diabetes mellitus is often called the silent killer because this disease can affect all organs of the body, which causes various complications. The duration of the disease, unstable blood sugar levels cause a variety of subjective complaints. This study aims to determine the relationship of disease duration and blood sugar levels with subjective complaints of type 2 diabetes mellitus sufferers at Putri Ayu Health Center, Jambi City. This research is a quantitative study with cross sectional research design. The population in this study was DM type 2 sufferers who were registered as outpatients in July 2019, amounting to 102 people with a total sample of 50 people with a sampling technique that is accidental sampling. Analysis in this study is univariate and bivariate, using the Mann-Whitney test, this research instrument uses observation sheets.The results of the univariate analysis showed that most respondents experienced subjective flaws, duration of illness in the long category (≥ 6.5 years) and stable blood sugar levels of the respondents. The results of the bivariate analysis showed that there was no significant relationship between the duration of the disease and blood sugar levels with subjective complaints with a p-value> 0.05. Based on this analysis it can be concluded that there is no relationship between the duration of the disease and blood sugar levels on subjective complaints in patients with Type 2 diabetes. Research suggestions are, to the health center to provide counseling related to subjective complaints of people with diabetes mellitus so that people with diabetes mellitus are more vigilant about complications diabetes mellitus in the form of counseling, counseling, posters, leaflets, banners and educational videos.